The macroeconomic consequences of subsistence self-employment - Juan Herre\~no; Sergio Ocampo Díaz (The University of Western Ontario, Department of Economics, 2023)
We evaluate the aggregate effects of expansions of credit supply in environments where subsistence self-employment is prevalent. We extend a standard macro development model to include unemployment risk, which becomes a key driver of selection into self-employment. The model is consistent with the joint distribution of earnings and occupations, the reaction of wages to labor demand shocks, and the small effects of expansions in the supply of microloans on the earnings of the self-employed. We find that the elasticity of aggregate output to expansions in credit supply is proportional to the elasticity of individual earnings. This proportionality arises due to the muted effects of wages in general equilibrium in the presence of subsistence self-employment, and is not present in models without subsistence self-employment due to a larger wage response, and a larger crowding-out of private savings in response to a higher availability of credit.
Keywords: E44; J25; O11; O16; O17; 330; Self-Employment; Unemployment; Development; Micro-Finance